The second silence - Goudge, Eileen (New York : Viking, 2000)
When Noelle Van Doren's only child is stolen from her by her wealthy estranged husband, it is she who must battle against an onslaught of false evidence, to prove she's a fit parent.
Keywords: Real estate developers -- Fiction; Parental kidnapping -- Fiction; Separated people -- Fiction; Divorced parents -- Fiction; Romantic suspense fiction